Transglutaminases 2015
DOI: 10.1007/978-4-431-55825-5_4
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Transglutaminase 2 Function Gained from Genetically Modified Animal Models

Abstract: Transglutaminase 2 (TG2) has been implicated in a number of physiological processes and in disease. A number of different types of genetically engineered mice have been generated to help understand the role and regulation of TG2 in physiology and pathology and to help delineate the molecular basis of its actions. This chapter will briefly review guidelines for animal husbandry and animal study design, TG2 mouse models and recent insights into the physiology and pathophysiology of TG2 that have come from the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…However, a definite correlation between TG function or deficiency and a specific pathology has been consistently demonstrated in only a few cases, examples of which are discussed below. Knockout mouse models have been useful to correlate the functional roles of FXIIIA, TG1, TG2, TG3, TG4, and protein 4.2 with various physiologic and disease mechanisms (7,8). No studies of knockout mice for TG5, TG6, or TG7 have been reported.…”
Section: Tgs and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…However, a definite correlation between TG function or deficiency and a specific pathology has been consistently demonstrated in only a few cases, examples of which are discussed below. Knockout mouse models have been useful to correlate the functional roles of FXIIIA, TG1, TG2, TG3, TG4, and protein 4.2 with various physiologic and disease mechanisms (7,8). No studies of knockout mice for TG5, TG6, or TG7 have been reported.…”
Section: Tgs and Diseasementioning
confidence: 99%
“…Shortcomings, in terms of reliability and reproducibility of mouse studies, alluded to above, are evident in some contradictory studies that have been reported for TG2 knockout mice, particularly in the areas of apoptosis, mitochondrial function, vascular remodeling, and neurodegenerative diseases (7,8). With respect to the latter, for example, despite TG2 being implicated in Huntington's disease pathogenesis for almost 20 yr, recent evidence from genetic ablation of TG2 in 2 different Huntington's disease models, where experiments were performed according to recommended guidelines for animal husbandry, indicates that TG2 deletion does not improve motor, cognitive, molecular, histologic, or lifespan phenotypes and is thus not an important factor in Huntington's disease pathology (8,47). However, neither the presence nor activities of TG isozymes were measured to rule out possible intracellular induction of other TG family members, such as TG1, that may contribute to intracellular crosslinking processes.…”
Section: Tg-mediated Crosslinking Of Crystallins Contributes To the F...mentioning
confidence: 99%
“…Targeted mutant mice, such as those with a gene knockout (KO), play a vital role in understanding the integrated physiological and pathological functions of a protein in a tissue-specific context [ 89 ]. Three TG2 KO mouse lines [ 90 , 91 , 92 ] were generated using genomic DNA from the 129 sub-strain to target the catalytic domain of the Tgm2 gene.…”
Section: Targeting Tg2 In Inflammation and Sepsis: Evidence From Kmentioning
confidence: 99%